Water Level Precision System Using IoT Enabled Sensing Technology - Zaruddin, Nurul Khairina Syarah; Syed Zahurul Islam, (Evolution in Electrical and Electronic Engineering, 2023)
Precision refers to the amount of information that is conveyed by a number in terms of its digits. It shows the closeness of two or more measurements to each other. It is independent of accuracy. For this system, two ultrasonic sensors are used to determine the reading of the water level. The author intends to show the closeness value of the water reading when there are two values from two sensors by placing two sensors. Next, solar energy is a process of converting light to electricity (voltage), called the photovoltaic (PV) effect. Currently, solar panels convert most of the visible light spectrum and about half of the ultraviolet and infrared light spectrums to usable solar energy. This project uses solar energy as the main supply to transfer the energy to the load and was created to monitor the water level, and the error value of the sensor, and notify the user when the water level is at an undesirable level using the Blynk application. Aside from that, improving data transmission and monitoring by implementing an IoT-enabled Blynk application is one of the project's goals. By using the Blynk Application, the data transmission can be transmitted smoothly, and the user is able to monitor the level of water anytime and anywhere, as long as there is an internet connection. Next, to examine the precision of two sensor data sets, a suitable formula is used to show the error value for sensor 1 and sensor 2. This is to ensure the accuracy of the water level in the flood-prone area.